Higher seroprevalence of hepatitis E virus in autoimmune hepatitis: Role of false‐positive antibodies. (9th January 2020) - Llovet, Laura‐Patricia; Gratacós‐Ginés, Jordi; Ortiz, Oswaldo; Rodriguez‐Tajes, Sergio; Lens, Sabela; Reverter, Enric; Ruiz‐Ortiz, Estibaliz; Costa, Josep; Viñas, Odette; Forns, Xavier; Parés, Albert; Londoño, María‐Carlota
Abstract: Background and aims: Recent studies have found an increase in the seroprevalence of hepatitis E virus (HEV) infection in patients with autoimmune hepatitis (AIH). We aimed to assess the prevalence of positive anti‐HEV IgM and IgG, and HEV‐RNA in a cohort of patients with AIH, to determine the impact of positive HEV serology on patient outcome, and to evaluate the role of hypergammaglobulinemia and positive autoantibodies in the presence of positive anti‐HEV serology. Methods: One hundred and five patients tested for HEV infection between 2014 and 2018 were included in the study: 50 with chronic AIH (more than 1 year on treatment), and 55 with an acute hepatitis (30 patients with acute AIH and 25 with non‐AIH). Results: Seroprevalence of HEV was higher in patients with acute AIH (17% vs 10% in patients with chronic AIH and 8% in patients with non‐AIH). Patients with acute AIH and positive anti‐HEV IgG were older (58 vs 40; P = .006), had higher IgG levels (27 g/dL vs 13 g/dL; P = .03) and antismooth muscle antibodies (ASMA) titres (1:160 vs 1:80; P = .045), and were more likely to have another autoimmune disease (60% vs 16%; P = .03). At the time of HEV testing, anti‐HEV IgG positive patients had significantly higher serum IgG levels (17 g/L vs 11 g/L; P = .009), ANA (1:160 vs 1:60; P = .026) and ASMA titres (1:80 vs 1:40; P = .021). Conclusion: Seroprevalence of HEV in patients with AIH in Catalonia does not differ from that of the general population. The higher HEV seroprevalence in patients with acute AIH with higher levels of gammaglobulins and high antibody titres suggest the presence of cross‐reactivity between HEV and liver antigens.